2013
DOI: 10.1007/s11434-013-5784-4
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of organic pollutants by a Co3O4-graphite composite electrode in an electro-Fenton-like system

Abstract: A novel composite electrode was constructed by pressing together Co 3 O 4 and graphite and it was used as the cathode in an electro-Fenton-like (EFL) system. The poor electron transport characteristic of Co 3 O 4 was overcome by incorporating graphite. In situ electro-catalytic generation of hydroxyl radicals (•OH) occurred at high current efficiencies from pH 2-10, extending the traditional Fenton reaction pH range. Cyclic voltammetry and AC impedance spectrometry were used to characterize the composite elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…Electrochemical impedance spectroscopy (EIS) is an in situ, rapid, and convenient method that can provide a nondestructive assessment of the corrosion behavior of a coating, and can also determine its corrosion mechanism (Liu et al, 2012(Liu et al, , 2013a. EIS curves for the ZrO 2 nanoparticle modifi ed epoxy coating samples were recorded using a Princeton 2273 electrochemical system.…”
Section: Corrosion Performance Of Zro 2 Nanoparticle Modifi Ed Epoxy mentioning
confidence: 99%
“…Electrochemical impedance spectroscopy (EIS) is an in situ, rapid, and convenient method that can provide a nondestructive assessment of the corrosion behavior of a coating, and can also determine its corrosion mechanism (Liu et al, 2012(Liu et al, , 2013a. EIS curves for the ZrO 2 nanoparticle modifi ed epoxy coating samples were recorded using a Princeton 2273 electrochemical system.…”
Section: Corrosion Performance Of Zro 2 Nanoparticle Modifi Ed Epoxy mentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15] Many studies have demonstrated that under sonication or irradiation, Fe3O4 nanoparticles (NPs) could decontaminate many organic pollutants. 16,17 Very recently, we showed that upon coating Fe3O4 NPs with a thin layer of carbon, Fe3O4 NPs catalyzed the Fenton-like reaction effectively without external energy supply.…”
Section: Introductionmentioning
confidence: 99%
“…The corresponding electrochemical parameters were listed in Table 2. From the Bode plots of Figure 5, there are two time constants occurred during the whole immersion times [15,16]. The capacitive semicircle at high frequency is associated with the rust layer absorbed on the electrode surface, and the capacitive semicircle at the medium-low frequency is attributed to the double layer capacitance and charge-transfer resistance [17,18].…”
Section: The Effect Of Temperature On Corrosion Behavior In Crs Solutmentioning
confidence: 98%